2017
DOI: 10.15208/beh.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Thai Select restaurant brand loyalty in the United Kingdom

Abstract: Abstract:This study examined the determinants of Thai Select restaurant brand loyalty which included restaurant brand image, staff service quality, perceived quality, brand awareness, and brand association on brand loyalty. Of the estimated 1,600 Thai restaurants within the United Kingdom, only 57 have been certified as having the authenticity and quality of Thai Select, which functions as a global branding effort for Thai restaurants by the Thai government. LISREL 9.1 was used to conduct a confirmatory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…This is because the significance value obtained in the t-test is below the minimum value of 0.05, which is 0.00. The results of this study are in line with research (Sornsaruht & Sawmong, 2017) that Customer Authentic Perception has a positive effect on Perceived Quality. These finding also align with (Phung et al, 2019) saying that the restaurant meets the customer's desire to experience authentic fastfood cuisine and service and is regarded as a better service.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is because the significance value obtained in the t-test is below the minimum value of 0.05, which is 0.00. The results of this study are in line with research (Sornsaruht & Sawmong, 2017) that Customer Authentic Perception has a positive effect on Perceived Quality. These finding also align with (Phung et al, 2019) saying that the restaurant meets the customer's desire to experience authentic fastfood cuisine and service and is regarded as a better service.…”
Section: Discussionsupporting
confidence: 90%
“…From the literature review and theory for perceived quality (PQ), the following observed variables were included in the study. These were identified as superior ingredients, delicious taste, and enticing smell (Sornsaruht & Sawmong, 2017).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…When a product is in process, the focus should be on customer relationships (Rust et al, 2000). Modern branding focuses on creating brand loyalty while building long-term relationships (Sornsaruht & Sawmong, 2017). Awan & Rehman (2014) see a unifying correlation between customer satisfaction and brand loyalty.…”
Section: Brand Loyaltymentioning
confidence: 99%